Pioneers : A Tale of Russian-Jewish Life in the 1880s - An-Ski, S., 1863-1920 (Book collections on Project MUSE., 2014)
"S.A. An-sky's novel dramatizes the dilemmas of Jewish young people in late Tsarist Russia as they strive to throw off their traditional religious upbringing to adopt a secular and modern identity. The action unfolds in the town of M. in the Pale of Settlement, where an engaging cast of characters wrestles with cultural and social issues. Their exploits culminate in helping a young Jewish woman evade an arranged marriage and a young Russian woman leave home so she can pursue her studies at a European university. This startling novel reveals the tensions and triumphs of coming of age in a revolutionary time"--Provided by publisher